Subclinical cardiotoxicity in childhood cancer survivors exposed to very low dose anthracycline therapy. Issue 1 (30th August 2014) - Leger, Kasey; Slone, Tamra; Lemler, Matthew; Leonard, David; Cochran, Cindy; Bowman, W. Paul; Bashore, Lisa; Winick, Naomi
<x xml:space="preserve">Abstract</x> Background Subclinical cardiotoxicity occurs in childhood cancer survivors following moderate and high anthracycline doses. However, less is known about the subclinical changes in left ventricular (LV) structure that occur after very low anthracycline doses of ≤100 mg/m2. This study was designed to assess LV function and key structural parameters following very low doses of anthracycline. Procedure Conventional 2‐dimensional echocardiograms with Doppler were obtained in 91 survivors of childhood cancer exposed to ≤100 mg/m2, an average of 9.8 years from diagnosis. LV structural measurements were converted into Z‐scores. The Z‐score distributions were compared to those of the normal population. Diastolic and systolic function were quantified. Results The cohort demonstrated a decreased posterior wall thickness (mean Z‐score −1.01) and mildly decreased LV end diastolic (mean Z‐score −0.85) and systolic (mean Z‐score −0.84) dimensions compared to the normal population (P < 0.001). Further, 28% of patients (n = 25) had abnormal LV posterior wall thickness, ≥2 standard deviations below the mean (Z‐score ≤ −2). There were no patients with diastolic dysfunction or symptomatic systolic dysfunction, however four patients demonstrated abnormal SF ≤ 28%. Conclusions A significant proportion of patients exposed to very low doses of anthracycline demonstrate subclinical abnormalities in LV structure, despite the absence of radiation or other risk factors. While we cannot say whether these structural changes will result in clinically significant cardiac disease, the reported progressive nature of these findings raises concern that there may truly be no safe dose of anthracycline. Pediatr Blood Cancer 2015;62:123–127. © 2014 Wiley Periodicals, Inc.